PENGARUH JENIS MATERIAL PAHAT POTONG DAN ARAH PEMAKANAN TERHADAP KEKASARAN PERMUKAAN BAJA EMS 45 PADA PROSES CNC MILLING (Effect Of Types Of Material Cutting Tool and Feeding Direction on The Surface Roughness Steel EMS 45 in the CNC Milling Process) - Widiantoro, Ana Wilda; Khumaedi, Muhammad; Sumbodo, Wirawan (Universitas Negeri Semarang, 2017)
AbstractThis study aims to: (1) Testing the effect of the material type of cutting tool to the surface roughness of steel EMS 45 in the CNC Milling. (2) Testing the effect of feeding direction on surface roughness of steel EMS 45 in the CNC Milling. (3) Testing the effect of the material type of cutting tool and feeding direction on the surface roughness steel EMS 45 in the CNC miiling Process.The method used is an experimental method with factorial design AxB where A is a types of material cutting tool while factor B is a feeding direction. Analysis of data using two-way analysis of variance with interaction in the application program SPSS 16.The final conclusion is that: (1) There is the influence of the material type of cutting tool on the surface roughness steel EMS 45 in the CNC Milling process. (2) There is the influence of feeding direction on the surface roughness steel EMS 45 in the CNC Milling process. (3) No effect beetwen the material type of cutting tool and feeding direction on the surface roughness steel EMS 45 in the CNC Milling process. Results of further tests Post Hoc Test namely: a) There was a significant effect of directions funeral unidirectional rotating 90o to the direction of the Z axis, b) There was a significant effect of directions burial direction of 45oto 90o and rotates in the direction of the Z axis, c) There was a significant effect of directions ingestion Z with a unidirectional rotating axis 90o and 45o in the same direction.